2022
DOI: 10.1029/2021jb023498
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence of Frequency‐Dependent Directivity Effects From Small‐To‐Moderate Normal Fault Earthquakes in Central Italy

Abstract: Directivity effect of an earthquake is the focusing of the radiated seismic wave energy due to the rupture propagation along the fault (Anderson, 2007;Ben-Menahem, 1961;Boatwright, 2007;Joyner, 1991). Earthquake directivity represents the analogue of the Doppler effect for sound and light waves (Douglas et al., 1988;Pacor, Gallovič, et al., 2016), which shifts the frequency of a moving oscillator to higher frequency when the oscillator moves toward an observer, and lower frequency when it moves away. This phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 100 publications
4
7
0
Order By: Relevance
“…The other studies did not investigate either spatial or temporal variability. Calderoni et al (2017), Wang et al (2019), andColavitti et al (2022) all investigated the azimuthal directivity of the larger earthquakes in the 2016-2017 Italy sequence and found them to be predominantly unilateral ruptures, Figure 1. Map showing the location of the earthquakes of this study (red circles), the strongest earthquake that occurred in the same source region during the 2009 L' Aquila seismic sequence (green circle), stations (black triangles) used in the analysis and focal mechanisms from Amatrice, Visso, and Norcia earthquakes are also included.…”
Section: 1029/2022jb025022mentioning
confidence: 99%
See 1 more Smart Citation
“…The other studies did not investigate either spatial or temporal variability. Calderoni et al (2017), Wang et al (2019), andColavitti et al (2022) all investigated the azimuthal directivity of the larger earthquakes in the 2016-2017 Italy sequence and found them to be predominantly unilateral ruptures, Figure 1. Map showing the location of the earthquakes of this study (red circles), the strongest earthquake that occurred in the same source region during the 2009 L' Aquila seismic sequence (green circle), stations (black triangles) used in the analysis and focal mechanisms from Amatrice, Visso, and Norcia earthquakes are also included.…”
Section: 1029/2022jb025022mentioning
confidence: 99%
“…(2019), and Colavitti et al. (2022) all investigated the azimuthal directivity of the larger earthquakes in the 2016–2017 Italy sequence and found them to be predominantly unilateral ruptures, distinctly different from the assumed bilateral circular models of the stress drop studies. Calderoni et al.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, wide-band ground motion simulation will be investigated and more scenarios covering a range of magnitudes and source parameters of basins will be computed, which will provide a better understanding of the seismic effect of the basin for detailed hazard assessment. And we will consider the source directivity effects (Wen et al, 2015;Convertito et al, 2016;Vincenzo et al, 2016;Ross et al, 2020;Colavitti et al, 2022) in our future research in more detail below.…”
Section: Comparison Between Simulated Time History and Observed Recordsmentioning
confidence: 99%
“…Pacor et al (2016) showed through a study using spectra of the aftershock records of the 2009 L'Aquila earthquake in central Italy that the rupture directivity effect is maximal above the corner frequency, and it subsequently decreases with increasing frequency. Using spectra from a large number of ground-motion records from central Italy, Colavitti et al (2022) showed that the rupture directivity effect is a band-limited phenomenon with a width of up to approximately five times the corner frequency. Although our study is concerned with the response spectra, the finding related to the large variability in a particular frequency range near corner frequencies is consistent with the findings of previous studies.…”
Section: Magnitude Dependencementioning
confidence: 99%